Framing Analysis Of The Zhongdang Pan & Gerald M. Kosicki Model Of The Vaccine Issue On The Online News Portal Tribunnews.com - Soni Sonjaya; Mohamad Irsandy; Rifqi Zaeni Achmad Syam (Jurnal Multidisiplin Sahombu, 2024)
This research discusses the phenomenon of vaccine news that has colored various mass media since the beginning of 2020, including online media. This has become a public spotlight because news about vaccine issues is considered very crucial. Tribunnews.com, regarding vaccine news that has been classified by news type, will be the object of research with a focus on the structure of framing analysis, namely: Syntax, Script, Thematic and Rhetorical as a reference to see how journalists construct a reality. In this study, the researcher uses a qualitative method with the Zhongdang Pan & Geral M. Kosicki analysis model and the Constructivism paradigm as a view that social life is not a natural reality, but a reality formed from the results of construction. This analysis is used to describe and understand how the four framing structures see the construction of news about vaccine issues. The results of this study show that the framing carried out by the online media Tribunnews.com towards the vaccine issue is how journalists construct news with the aim of guiding public opinion related to the vaccine issue, which is considered very crucial at this time, the Tribunnews.com media also emphasizes the highlighting of the issue that vaccines are one of the obligations that must be carried out by the public at this time.